Impatiens shennongensis (Balsaminaceae): a new species from Hubei, China - Wang, Qian; Gadagkar, Sudhindra R.; Deng, Hong-Ping; Yang, Zhi-Ming; Yu, Feng-Qiong (Phytotaxa, 2016)
A new species of the genus Impatiens is described from Hubei province, China. Although it shares some features with I. dicentra, such as single-flowered peduncles and a filamentous bristle terminating the upper of the lateral united petals, it possesses distinct traits such as shorter plant height, rhombic to sub-rhombic leaves, lateral sepals entire, and lower sepals navicular without a spur. We believe that this is a new addition to the speciose Impatiens genus, and propose the name Impatiens shennongensis Q. Wang & H.P. Deng. We also describe the new species in this paper in terms of SEM-based seed and pollen micromorphology.